Finotonlimab (PD-1 inhibitor) plus bevacizumab (bevacizumab biosimilar) as first-tier therapy for late-stage hepatocellular carcinoma: a randomized phase 2/3 trial - Chuanhua Zhao; Yanqiao Zhang; Gang Wang; Jinfang Zheng; Weiqing Chen; Zheng Lu; Li Zhuang; Shanzhi Gu; Lei Han; Zhendong Zheng; Zujiang Yu; Yongsheng Yang; et al. (Signal Transduction and Targeted Therapy)
Abstract We aimed to assess the tolerability and efficacy of finotonlimab (an anti-programmed cell death protein-1 antibody) in combination with SCT510, a bevacizumab biosimilar, versus sorafenib in unresectable advanced HCC. This randomized phase 2 and 3 study (ClinicalTrials.gov, NCT04560894; Chinadrugtrials.org.cn, CTR20201976 and CTR20201974) was performed at 67 hospitals in China. HCC patients (n = 398) were included between 11 November 2020 and 28 September 2022. In phase 2, patients received intravenous finotonlimab (200 mg every 3 weeks) combined with SCT510 (15 mg/kg every 3 weeks). In phase 3, 346 patients were randomized (2:1) to either the finotonlimab plus SCT510 (dual-agent) group or the sorafenib group. The median follow-up time for the dual-agent therapy and sorafenib groups was 19.9 and 19.0 months, respectively. Median PFS, assessed by BICR according to RECIST 1.1, was significantly longer in the dual-agent group (7.1 months [95% confidence intervals CI: 6.1, 8.4]) than in the sorafenib group (2.9 months [95% CI: 2.8, 4.1]; stratified hazard ratio [HR]: 0.5, 95% CI: 0.38, 0.65, p < 0.0001). Median OS was also significantly longer in patients receiving finotonlimab plus SCT510 (22.1 months [18.6, not available]) than in those receiving sorafenib (14.2 months [95% CI: 10.2, 15.8]; HR: 0.60 [95% CI: 0.44, 0.81], p < 0.0008). Finotonlimab in combination with bevacizumab demonstrated favorable efficacy, in comparison to sorafenib, as a first-line treatment for unresectable HCC, with a manageable safety profile.